Comparing treatment modalities for transplant kidney vesicoureteral reflux in the pediatric population. Issue 6 (December 2018) - Sheth, K.R.; White, J.T.; Stanasel, I.; Janzen, N.; Mittal, A.; Koh, C.J.; Austin, P.F.; Roth, D.R.; Tu, D.D.; Gonzales, E.T.; Ryan, S.; Jorgez, C.; et al.
Summary: Introduction: Non-refluxing ureteral reimplantation is favored in pediatric renal transplantation to prevent complications, such as vesicoureteral reflux (VUR) in the transplant ureter. VUR resulting in febrile urinary tract infections remains a problem in this population, leading to repeated hospitalizations and increased morbidity. Revision of the vesicoureteral anastomosis can be a surgical challenge due to scar tissue and tenuous vascularity of the transplant ureter. Therefore, alternative options such as endoscopic injection of Deflux at the neo-orifice and surveillance with prophylactic antibiotics have emerged as potential treatment modalities for transplant ureter VUR. Objective: The authors reviewed their experience of the management of VUR in the transplant ureter, comparing outcomes of various modalities. Study design: With Institutional Review Board approval, a retrospective chart review of all renal transplant patients from January 2002 to January 2017 was conducted. All patients with VUR on voiding cystourethrogram (VCUG) after surgery were identified. Indications for end-stage renal disease, urologic comorbidities, pretransplant VCUG, and operative details were recorded. After transplantation, febrile urinary tract infections, ultrasound findings, and any further interventions—surveillance, subureteral endoscopic injection of Deflux, or ureteral reimplantation—were documented along with their outcomes. Results: Overall, VUR was identified in 35/285 (12.3%) transplant patients after a non-refluxing ureteroneocystostomy. VUR was managed with surveillance in 17/35 (49%), intravesical Deflux injection in 11/35 (31%), and immediate redo ureteral reimplantation in 7/35 (20%). Ten out of 11 patients undergoing Deflux injection had a postoperative VCUG. All patients developed VUR recurrence; the majority showed immediate failure and only 1/10 showed late recurrence. Of the immediate failures, 3/9 patients were maintained on prophylactic antibiotics, and 6/9 patients underwent ureteral reimplantation. In these six patients undergoing reimplantation after failed Deflux, 3/6 (50%) patients required additional surgeries: One patient developed recurrence of reflux and two patients developed ureterovesical junction obstruction. In contrast, no complications were seen in patients undergoing primary ureteral reimplantation. Discussion: The study is limited by low numbers and a retrospective design. However, the results of this study differ significantly from the published Deflux series showing a success rate of more than 50% in the treatment of transplant kidney VUR. In fact, post-Deflux redo ureteral reimplantation was associated with an increased risk of postoperative complication. Conclusion: The use of Deflux in the post-transplant setting has poor results. In the study series, 11/11 patients demonstrated clinical and radiographic failure. Therefore, as an institution the authors do not recommend Deflux as first-line treatment of VUR in the transplant patient. Extended Summary Figure Treatment flowchart for transplant kidney vesicoureteral reflux (VUR).